Sensors for Everyday Life Environmental and Food Engineering - Mukhopadhyay, Subhas Chandra; Postolache, Octavian Adrian; Jayasundera, Krishanthi P.; Swain, Akshya K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers an up-to-date overview of the concepts, modeling, technical and technological details and practical applications of different types of sensors, and discusses the trends of next generation of sensors and systems for environmental and food engineering. This book is aimed at researchers, graduate students, academics and industry professionals working in the field of environmental and food engineering, environmental monitoring, precision agriculture and food quality control.
Determination of NOx and Soot Concentrations Using a Multi-Wavelength Opacimeter -- Development of the Atomic Emission Spectroscopy System Using Helium-Microwave-Induced Plasma for Fine Particles on Environmental Monitoring -- Real-Time HVAC Sensor Monitoring and Automatic Fault Detection System -- High Sensitivity Optical Structures for Relative Humidity Sensing -- Oxygen Gas Sensing Technologies Application: A Comprehensive Review -- Application of Practical Nitrate Sensor Based on Electrochemical Impedance Spectroscopy.
Keywords: Electronics; Environmental monitoring; Agriculture; Biotechnology; Electronics and Microelectronics, Instrumentation; Environmental Monitoring; Agriculture; Chemical Bioengineering